Synthetic Utility of Aminomercapto[1,2,4]triazoles in the Preparation of Fused Triazoles - Riyadh, Sayed M.; Abolibda, Tariq Z.; Sayed, Abdelwahed R.; Gomha, Sobhi M. (Current Organic Chemistry, 2022)
Triazoles and their fused derivatives are regarded as one of the most pharmacologically significant pillars due to their potent, broad, and numerous activities. This current review presents recent progress in the synthetic utility of 3-substituted-4-amino-5-mercapto[1,2,4]- triazoles as building blocks for a diverse range of fused [1,2,4]triazoles with pharmacological interest eg. pyrazolo-triazoles, triazolo-thiadiazoles, triazolo-triazoles, triazolo-thiadiazines, triazolo-triazines, triazolo-tetrazines, triazolo-thiadiazepines, and others. The biological activity of some triazoles and their fused derivatives are also presented. This suggests that triazoles can be particularly promising synthons in synthesis of functionalized heterocyclic compounds used in the design of novel, highly effective pharmaceuticals with a broad spectrum of bioresponses. All of these topics are drawn in this review from the period from 2000 to 2020.
Keywords: 4-triazoloazines